Jehovah’s witness patient undergoing major surgery: Methods to minimize blood loss - T Kumaravadivel Dharmalingam; Liew, Constance Sat Lin; Rajesh Kumar Muniandy (Gazi University Medical Faculty, 2020)
Jehovah's Witnesses are a group of people who refuses to get blood transfusions and blood products due to their faith. Due to this, Jehovah's Witness patients who are planned for major surgical procedures are always a challenge for both surgeons and anaesthetist. Surgical and anaesthetic techniques must be aimed at minimising blood loss. We are reporting a peri-operative management for a Jehovah's Witness patient scheduled for a major surgery. This article emphasizes the techniques to minimize blood lose, in order to avoid blood transfusion.